A project zero model classroom in a Malaysian culture / Normah Abdullah, Laura Christ Dass and Siti Akmar Abu Samah - Abdullah, Normah; Christ Dass, Laura; Abu Samah, Siti Akmar (Universiti Teknologi MARA Shah Alam, 2017)
This paper is taken from a bigger study aimed at trialing a Western learning model in a Malaysian context where it is yet to be tested by previous research. The Visible Thinking (VT) Project of Project Zero research is used as benchmark for this study. A summary of selected PZ research projects presented in this paper highlights the learning benefits of establishing patterns of thinking within the classroom as projected by PZ studies of Harvard Graduate School of Education, the hallmark institution. Many aspects of classroom teaching have been shown by PZ research to enhance learning, this paper will focus on a Malaysian undergraduate classroom that has decided to trial this highly recommended model using a framework derived from PZ school settings. Part of the focus of the study was to check if the ideas and paradigms are transferable to a Higher Education ESL context of a culturally different setting in terms of the manifestations of classroom interactions, students’ and teacher’s perception of it as well as from the researcher’s observation of this classroom in session. The literature on the findings of VT project, mainly the thinking routines employed, the importance of establishing thinking routines in the classroom and examples of instances where these routines were visible in the classroom contexts are the summarized in this paper. Most of PZ research was conducted in school classrooms in a Western setting. This study prides itself in taking PZ research to a whole new level to study undergraduate students in a Malaysian classroom setting.